Teaching of Forensic Dentistry in Khartoum, Sudan - Sarah Hag Ali; Ademir Franco; Emilio Nuzzolese; Scheila Mânica (MDPI AG, 2024)
Background: Dental professionals assist with legal and criminal matters through the practice of forensic dentistry which has evolved over the past century and is now a crucial component of undergraduate dental education in many nations. The need for formal training in the subject and its inclusion in dental curricula were acknowledged and addressed in the 1960s and 1970s. Aims: This study aimed to investigate the teaching of forensic dentistry in dental universities of Khartoum, Sudan, and to propose certain topics and teaching criteria to be standardized in forensic dentistry teaching in Sudan. Materials and methods: An observational, descriptive study was conducted, involving all undergraduate dental institutions in Khartoum, Sudan. Institutional websites were searched using the Google search engine to obtain the dental program curricula in English. The curricula were then analyzed to identify the presence of forensic odontology/dentistry teaching. Results: Of the 19 universities included in the study, five (26.3%) teach forensic dentistry in their undergraduate curricula, whereas 12 (63.1%) do not. Two universities (10.6%) indicated the presence of forensic dentistry teaching in their curricula but did not provide actual instruction. The teaching of forensic dentistry mainly occurred during the second, third, and fourth years of the dental program. Three universities considered it an independent subject, while two universities incorporated it into oral and maxillofacial pathology. Four universities provided lectures only, while one university combined lectures and practical sessions. Qualified forensic dentists taught the subject in four universities, while one university had general dentists as instructors. The main topics delivered are: (1) introduction to forensics, (2) human identification, (3) dental age estimation, (4) interpretation of bitemarks, (5) DNA in forensics, and (6) child abuse. Conclusion: Forensic dentistry training is currently undervalued in Sudan due to various limitations. It is recommended that all dental schools in Sudan offer opportunities for students to learn and become acquainted with forensic dentistry as part of their dental programs. The Sudanese Dental Council should establish formal coordination with academic institutions and experienced forensic dentists to ensure the quality and relevance of the proposed modular course within the educational system. Finally, additional topics including dental record-keeping and dental malpractice are suggested for inclusion in the current modules.